2017
DOI: 10.3390/socsci6040154
|View full text |Cite
|
Sign up to set email alerts
|

Effort and Reward Effects: Appreciation and Self-Rated Performance in e-Internships

Abstract: Abstract:As new work and internship options arise, educators, employers and students seek information about the learning benefits of these new arrangements. This is also the case in terms of e-internships. The purpose of this study was to assess the merit of the effort-reward imbalance model to understand appreciation and performance as reported by the e-interns (also known as virtual interns). The study involved a cross-sectional sample of e-interns. The sample was recruited using the snowball technique and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Self-management techniques are give in the form of self-monitoring where students are trains able be able to observe their own behavior and record it (Wilmot et al, 2016), self-contracting so students can promise themselves, stimulus control where students are train able be able to control stimuli to reduce desired behavior (Ferguson et al, 2015) and self-reward where students are trained the self-reward strengthen behavior through self-reward (Jeske & Axtell, 2017). he provisions of self-management techniques is done through group counseling for eight sessions, to help the counselee be responsible for the manager negative activities, can change negative behavior and develop (Briesch DuBois et al, 2017).…”
Section: Graph 1 Results Of Pre-test and Post-test Scoresmentioning
confidence: 99%
“…Self-management techniques are give in the form of self-monitoring where students are trains able be able to observe their own behavior and record it (Wilmot et al, 2016), self-contracting so students can promise themselves, stimulus control where students are train able be able to control stimuli to reduce desired behavior (Ferguson et al, 2015) and self-reward where students are trained the self-reward strengthen behavior through self-reward (Jeske & Axtell, 2017). he provisions of self-management techniques is done through group counseling for eight sessions, to help the counselee be responsible for the manager negative activities, can change negative behavior and develop (Briesch DuBois et al, 2017).…”
Section: Graph 1 Results Of Pre-test and Post-test Scoresmentioning
confidence: 99%
“…Specifically, it is proposed that when technology is employed effectively to balance the needs of the business with the needs of the e-interns, psychological contracts in virtual internships may take more positive forms, reflecting mutually supportive relationships that provide room for skill and personal development. Some evidence for the importance of relationships in e-internships and e-interns' personal and skill development comes from recent work that showed that e-interns feel more appreciated and valued by their employees when they receive training and potentially also remuneration (Jeske & Axtell, 2017). In this paper, we explore which (structural and technology-specific) characteristicssuch as communication frequency -may contribute to the creation of more relational and balanced relationships in virtual internships.…”
Section: Psychological Contracts and E-internships: Research Questionsmentioning
confidence: 96%
“…This means that these virtual interns and the organization are often located in different cities, countries, and even time zones. Many interns complete such internships to gain work experience or complete projects for academic credit [ 4 ]. Due to the ease of locating suitable talent for research projects, such internships are also of interest to many academics who seek suitable and motivated talent for research projects.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual interns have often self-reported lower performance when they lack goal clarity and supervisory support. In addition, support satisfaction correlates positively with goal clarity and interns feeling valued [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation